Communication on Climate Change in the Mediterranean by Non-State Actors: A Framing Analysis - Iosif Botetzagıas; Emre İşeri (Alternatif Politika)
How do non-state actors frame climate change in a region labelled as a climate hotspot? To answer this question, this article explores the climate communication strategies of non-state actors with various country origins. Adopting the quantitative content analysis method, it comparatively analyses differing frame utilizations (e.g. ecological/meteorological, policy, economic and energy interests, culture, science and technology, civil society) of non-state actors in their selected climate change/global warming-related reports (n=89) on the Mediterranean. The findings provide clues on the cosmopolitan framing of non-state actors on the regional level.